Pengembangan Empati Mahasiswa Calon Guru Madrasah Ibtidaiyah - Murdianto Murdianto (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2018)
Abstract: Numerous acts of violence, war, suffering, loneliness, racism and other social diseases show the world that loss of empathy. Under these conditions a great empathy needed to help with the situation that is happening. Not least in schools, the various phenomena of violence and action that caused loss of empathy also have occurred. Fostering empathy for a teacher is an important task performed by MI’s teachers candidates education board to respond the phenomenon. Bibliotherapi techniques can be developed in learning and other settings indeveloping empathy teachers candidates. Key words: Biblioterapi and empathy, learning, teacher.